Physically Large Displays Improve Path Integration in 3D Virtual Navigation Tasks - Tan, Desney; Gergle, Darren; Scupelli, Peter G.; Pausch, Randy ((2004) CHI 2004 Conference on Human Factors in Computing Systems,, 2004)
Previous results have shown that users perform better on spatial orientation tasks involving static 2D scenes when working on physically large displays as compared to small ones. This was found to be true even when the displays presented the same images at equivalent visual angles. Further investigation has suggested that large displays may provide a greater sense of presence, which biases users into adopting more efficient strategies to perform tasks. In this work, we extend those findings, demonstrating that users are more effective at performing 3D virtual navigation tasks on large displays. We also show that even though interacting with the environment affects performance, effects induced by interactivity are independent of those induced by physical display size. Together, these findings allow us to derive guidelines for the design and presentation of interactive 3D environments on physically large displays.